Osmotic Dehydration of Apples Under Reduced Pressure Conditions (Agricultural Engineering, 2016)
The aim of the study was to determine the effect of reduced pressure on the osmotic dehydration of apples. Tests were performed under vacuum of 8 kPa, 67 kPa, 80 kPa and under the atmospheric pressure (100 kPa). The samples were dehydrated in a sucrose solution with a concentration of 30°Bx, 50°Bx and 70°Bx. It has been shown that the effect of low pressure application depends significantly to the concentration of the osmotic solution. It has been found that the overall weight change significantly depend on the concentration of the solution, and after 3 hours of dehydration at a pressure of 80 kPa at solutions of 30°Bx, 50°Bx and 70°Bx total weight loss increased by 65%, 12% and 25% respectively, when compared to samples dehydrated at atmospheric pressure. From the studied variants of reduced pressure, the pressure of 80 kPa seems to be the optimal one, as evidenced by the lowest values of weight gain to water loss ratios for apples dehydrated in solutions of 50°Bx and 70°Bx.